Potential Interaction of Phorid Fly Megaselia scalaris (Loew) with Various Economically Important Arthropod Fauna - Kaushik Pramanik; Amit Layek; Debashis Mandal; Pranab Debnath; Debashis Roy (Research Highlights in Agricultural Sciences Vol. 4, 2022)
The ‘scuttle-fly’, Megaselia scalaris [1] (Diptera: Phoridae), is a tiny, synanthropic, polyphagous fly that may occupy a wide range of ecological niches. Under laboratory and natural conditions, various life cycle stages devour, parasitize, and consumed a larger variety of plant and animal materials. In mechanically barricaded environments, they are amongst the first wave of insects visiting human corpses. It is usually used in research and within the lab because it is easily cultured and this species is used in experiments involving developmental, genetic, and bioassay analyses. This species is important in the study of forensic entomology because evidence derived from the lifecycle and behaviour of these flies is useful in both medico-criminal and neglect/abuse cases. The objective of this study is to represent the association of this fly with a few agricultural and nonagricultural pests along with some social and eusocial insects where it is shown that for different insects, this fly has different mechanisms and modes of action. The diverse collaboration of this fly with these insects gives us clear knowledge of trophic interactions among species and contributes to the understanding structure of biodiversity and ecosystem functioning.